2007
DOI: 10.1248/cpb.55.268
|View full text |Cite
|
Sign up to set email alerts
|

Revised Structures of Gambiriins A1, A2, B1, and B2, Chalcane-Flavan Dimers from Gambir (Uncaria gambir Extract)

Abstract: Gambir, an official pharmacopoeic medicine in Japan, is the aqueous extract of the leaves and young twigs of Uncaria gambir ROXB. (Rubiaceae).2) The extract has been used for the treatment of diarrhea and sore throat as an astringent medicine in Southeast Asia, 3) and also for hoarseness, as an ingredient of the kampo medicine "Kyoseihatekigan."Flavan monomers, (ϩ)-catechin (1) and (ϩ)-epicatechin (2), 4) several other dimeric compounds 5) related to 1, as well as alkaloids, 6,7) have been reported to be the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 8 publications
6
56
0
Order By: Relevance
“…Uncaria gambir Proanthocyanidins: gambiriins A1-A2 ; gambiriins B1-B2; (+)-catechin; (+)-epicatechin; procyanidin B1; procyanidin B3; gambiriin [146] Uncaria glabrata Monoterpene indole alkaloids: 14α-hydroxyrauniticine; rauniticine; uncarine C-E; glabratine; deoxycordifoline [147] Indole alkaloid: ajmalicine Oxindole alkaloids: formosanine or uncarine B; isomitraphylline; mitraphylline [148] Triterpenes: Triterpenes: oleanolic acid; 3β,6β,19α-trihydroxyurs-12-en-28-oic acid [170] Triterpenes: 3β,6β,19α-trihydroxyurs-12-en-23-al-28-oic acid; 3β,19α-dihydroxy-6-oxo-urs-12-en-23-al-28-oic acid; 3β,19α-dihydroxy-6-oxo-urs-12-en-23-ol-28-oic acid [171] Triterpene: 23-nor-24-esomethylene-3β,6β-19α-trihydroxyurs-12-en-28 oic acid; 3β,6β,19α-trihydroxyurs-12-en-28-oic acid; 3-oxo-6β,19α-dihydroxyurs-12-en-28 oic acid; oleanic acid [192] Triterpenes: pomolic acid methyl ester; ursolic acid methyl ester; oleanolic acid methyl ester [193] Alibertia sessilis…”
Section: Nauclea Latifoliamentioning
confidence: 99%
“…Uncaria gambir Proanthocyanidins: gambiriins A1-A2 ; gambiriins B1-B2; (+)-catechin; (+)-epicatechin; procyanidin B1; procyanidin B3; gambiriin [146] Uncaria glabrata Monoterpene indole alkaloids: 14α-hydroxyrauniticine; rauniticine; uncarine C-E; glabratine; deoxycordifoline [147] Indole alkaloid: ajmalicine Oxindole alkaloids: formosanine or uncarine B; isomitraphylline; mitraphylline [148] Triterpenes: Triterpenes: oleanolic acid; 3β,6β,19α-trihydroxyurs-12-en-28-oic acid [170] Triterpenes: 3β,6β,19α-trihydroxyurs-12-en-23-al-28-oic acid; 3β,19α-dihydroxy-6-oxo-urs-12-en-23-al-28-oic acid; 3β,19α-dihydroxy-6-oxo-urs-12-en-23-ol-28-oic acid [171] Triterpene: 23-nor-24-esomethylene-3β,6β-19α-trihydroxyurs-12-en-28 oic acid; 3β,6β,19α-trihydroxyurs-12-en-28-oic acid; 3-oxo-6β,19α-dihydroxyurs-12-en-28 oic acid; oleanic acid [192] Triterpenes: pomolic acid methyl ester; ursolic acid methyl ester; oleanolic acid methyl ester [193] Alibertia sessilis…”
Section: Nauclea Latifoliamentioning
confidence: 99%
“…In research the content of catechins ranged from 14.76% to 54.97%. The results of Taniguchi et al (2007) found that from 31 gambier samples collected from gambier traders in 4 countries, Japan, Indonesia, Singapore, and China, it was known that catechin content ranged from 0.17 g to 0.76 g per 1 g sample with the average of 0.43g / g or 43%.…”
Section: Analysis Of Gambier:-based Onmentioning
confidence: 99%
“…Gambir is mainly composed of cattechu-tanic acid (a tannin), (+)-catechin (see Figure 2), (+)epicatechin, dimeric proanthocyanidins, procyanidins B1 and B3, and gambiriins A1, A2, B1, B2 and C (Taniguchi et al, 2007), much of them 3´,4´,5,7-tetrahydroxysubstituted derivatives of 3,4dihydro-2-phenyl-2H-1-benzopyran.…”
Section: [Figure 1]mentioning
confidence: 99%